2019
DOI: 10.1111/nep.13665
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral arterial stiffness is correlated with intrarenal arteriolosclerosis according to biopsies from patients with kidney disease

Abstract: Aim To investigate the possible associations between intrarenal arteriolosclerosis as determine by renal biopsy and endothelial function as well as arterial stiffness measured by peripheral arterial tonometry (EndoPAT). Methods This was a cross‐sectional study. Patients who underwent both renal biopsy and EndoPAT were recruited, and intrarenal arteriolosclerosis was graded according to the pathological slice. Endothelial function and arterial stiffness were both measured by EndoPAT and were expressed by the re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 28 publications
(48 reference statements)
0
7
0
Order By: Relevance
“…The test was performed once per patient by skilled investigators following the protocol instructions. 19 Participants were tested at a temperature of 21…”
Section: Vascular Function Measurementmentioning
confidence: 99%
“…The test was performed once per patient by skilled investigators following the protocol instructions. 19 Participants were tested at a temperature of 21…”
Section: Vascular Function Measurementmentioning
confidence: 99%
“…However, further works [20] revealed that high-resolution radial IMT can compete against carotid IMT in evaluating arterial remodeling burden and that it is also related to previous cardiovascular disease (CVD) and ischemia. An interesting study in renal artery biopsies reported a positive relationship between renal arteriosclerosis and augmentation index, a surrogate for peripheral arterial stiffness [21]. The main limitation of this study was borderline subject age for better performance of augmentation index [12].…”
Section: Introductionmentioning
confidence: 75%
“…First, intrarenal arteries are associated with generalized atherosclerosis when different measurements are used. 21 Second, arterial stiffness and CKD share similar risk factor profiles, such as age, gender, blood pressure, proteinuria, and so on. However, we found that the association between arterial stiffness and CKD outcomes remained significant after those risk factors were taken into consideration in analyses, which means that there are potential risks underlying these two pathophysiological processes.…”
Section: Discussionmentioning
confidence: 99%
“…However, there are some potential explanations. First, intrarenal arteries are associated with generalized atherosclerosis when different measurements are used 21 . Second, arterial stiffness and CKD share similar risk factor profiles, such as age, gender, blood pressure, proteinuria, and so on.…”
Section: Discussionmentioning
confidence: 99%